Pengaruh kinerja ekonomi dan manajemen bank - Merissa Rizki Arviana Bachri; Ardi Paminto; Irsan Tricahyadinata (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Bank is an institution that acts as a financial intermediary between parties who have the funds with the parties who need funds as well as an institution that serves to facilitate the flow of payment traffic. Therefore, banks must maintain public confidence and are required to achieve high profitability because profitability describes the success of management in generating profits.This study aims to determine the effect of economic performance factors and bank management factors seen from the financial ratios to the profitability of Bank Persero in Indonesia during the period 2007-2015. While the factor of bank management is measured through Debt to Equity Ratio (DER) as X1 and Current Ratio as X2 Economic performance factors are described by the interest rate of Bank Indonesia (BI rate) as X3 and inflation as X4. The profitability of Bank Persero is measured through Return on Assets (ROA) as Y.The object of research in this study is a banking company Persero listed in Indonesia Stock Exchange Period 2007-2015 (9 years). Where the analytical tool used is multiple linear regression analysis.Result of research indicate factor of economic performance, BI rate have positive influence and not significant to ROA. Similarly, inflation shows a positive and insignificant effect on ROA.While the bank management factor, DER has a negative and significant influence on ROA. While Current Ratio have negative effect and not significant to ROA